C-Kit, CD34 & α-SMA Immunohistochemical Features in Classic Kaposi Sarcoma and Kaposiform Hemangioendothelioma. Issue 1 (March 2017) - Hasby, Eiman A.; Mashad, Nehal El; Eltatawy, Rania
Abstract: Purpose & Methods: The aim of this work was to study the clinicopathological features of Kaposi sarcoma (KS) & kaposiform hemangioendothelioma (KHE) and analyze their immunohistochemical expression of c-Kit, CD34, α-SMA. The study was performed on cutaneous 10 classic KS & 8 KHE. Results: KHE shows several dilated lymphatic channels, focal capillary formation, lack of nuclear atypia and mitosis within tumor cells. These features help to exclude Kaposi sarcoma in spite of the kaposiform pattern of tumor cells. C-Kit was expressed by tumor cells in all KHE cases and in 60% only of KS. All elements within both tumor groups expressed CD34 antibody. α-SMA was expressed by tumor cells in 70% of KS cases and none of KHE. Conclusion: C-Kit and CD34 seem to be reliable at labeling KS and KHE as they can help in diagnosis of these tumors in routinely processed tissue but they don't differentiate between them. If α-SMA also labeled the tumor, then KHE diagnosis can be ruled out. KS & KHE exemplify stem cell tumors that could give smooth muscle cell–like phenotype in KS. Anti C-kit therapy should be tested in KS & KHE to prevent recurrence.